The implementation of the law on seat belt usage in Malaysia: a comparative study with Australia / Norazman Shah Abdullah, Fatimah Hani Ali and Ayob Mohd Zainuddin. - Abdullah, Norazman Shah; Ali, Fatimah Hani; Mohd Zainuddin, Ayob (2009)
The seatbelt law in Malaysia has been in existence since 1979 which is thirty years. Despite the introduction of the new rear seatbelt law to supplement the old existing law, the existing seatbelt laws should be reviewed to ensure that the law remains effective and proven to be life saver for car occupants. Comparison was made with Australian seatbelt laws to examine the possibility of adopting the Australian principle of laws or appropriate provisions with regards to the law of seatbelt usage into the Malaysian scenario. The Malaysian seatbelt laws were found to be non-comprehensive as it has not been reviewed for 30 years except for the recent introduction of the rear seatbelt law. The contents of the law are generally addressed without specification on certain matters for example on child restraint and pregnant women. Issues of liability of drivers on omission by passengers and punishment on repeated offenders have never been discussed in Malaysian seatbelt law. Adopting Australian seatbelt laws into our Malaysian seatbelt laws will help Malaysia in its development of the laws to ensure that car occupants' safety will always become a priority. The improvement of the Malaysian seatbelt law is to enhance the level of compliance of the laws among car users and passengers.